Metal Filled Nanostructured Silicon With Respect to Magnetic and Optical Properties - Granitzer, Petra; Rumpf, Klemens (Frontiers in Physics, 2020)
Within this work the utilization of nanostructured silicon as host material for filling with various magnetic nanostructures is reviewed whereas the magnetic and optical properties of the gained composite systems are elucidated. The metal filling of the pores is mainly performed by electroless deposition or by electrodeposition which is discussed by means of some examples. Furthermore, two different types of porous silicon (PSi) morphology are used for the deposition procedure. On the one hand microporous silicon offering luminescence in the visible range is utilized as template material. It offers a branched morphology with a structure size between 2 and 5 nm. In this case not only the magnetic response is investigated but also the influence of the metal filling on the optical properties. On the other hand mesoporous and macroporous silicon in it's low pore regime is employed which offers straight pores with diameters up to 90 nm. In this case the magnetic response strongly depends on the size, the geometry and the spatial distribution of the metal deposits within the pores. A crucial role plays also the morphology of the porous silicon, especially the distance between adjacent pores which is an important parameter regarding magnetic interactions.